Social Realism Project on Brings Back Knowledge into Curriculum Policy Making - Subkhan, Edi (Universitas Negeri Semarang, 2020)
The significant change in curriculum policy shifts the orientation of how to develop the curriculum no longer based on subject-matter but prioritizes competency as a basis. In Indonesia, for example, in 2004 the government officially issued a new curriculum policy called Competency-based Curriculum in which emphasizes competency or skills as the most important things that the students should gain. According to Priestley and Biesta (2013), this phenomenon is common throughout the world, not only in Indonesia but also in Scotland, UK, Australia, New Zealand, and many more. Curriculum that emphasizes more on skills or competencies than knowledge gained much criticism from many scholars. One of the most prominent criticisms comes from scholars’ groups who hold strongly social realism as an epistemological foundation. They have a vision to bring back the knowledge into curriculum policy making, because the imbalance of the curriculum more on skills will lead the students to lose the aims, purposes, and direction of education they got involved in. Amidst this issue, Barrett and Rata (2014) published an edited book comprising several articles under the spirit of bringing back knowledge into the curriculum.